Carbon sources derived from maize cobs enhanced nitrogen removal in saline constructed wetland microcosms treating mariculture effluents under greenhouse condition. (March 2020) - Li, Meng; Sun, Linlin; Song, Xiefa
Abstract: This study investigated an alternative carbon source derived from maize cobs (MCs) to enhance nitrogen removal in saline constructed wetlands (SCWs). The main objectives were to select the proper pretreatment method of MCs for rapid carbon release; and to investigate the effects of maize cob pieces (i.e. MCP) and three addition levels of maize cob lixiviums (i.e. L-MCL, M-MCL and H-MCL) on nitrogen purification performance and microbial characteristics of SCWs. Results showed NaOH pretreatment enhanced carbon release of MCs in seawater (from 7.5 ± 0.4 mgCOD g −1 to 16.4 ± 0.2 mgCOD g −1 ). The 80-d trial showed SCWs with M-MCL addition performed well on nitrogen removal: NO3 –N, 88.8 ± 11.6%; NO2 –N, 91.1 ± 3.5%; TAN, 96.5 ± 1.6%; TIN, 89.8 ± 10.4%; with 2 mg L −1 effluent COD. Denitrification parameters confirmed MCL to be a high quality carbon source: denitrification potential (PDN ) = 0.16 gN gCOD −1 ; heterotrophy anoxic yield coefficient (YH ) = 0.54 gCOD gCOD −1 . The MCP and H-MCL treatments improved substrate dehydrogenase activity, indicating a higher microbial activity in these SCWs. Sequencing analysis revealed that, regardless of addition manners, carbon sources from MCs changed the rhizosphere microbial community. At genus level, Anaerophaga (10.1%), Granulosicoccus (8.2%) and Sulfurimonas (6.6%) dominated in SCWs under MCP treatment. Increased MCL addition levels improved the relative abundance of Vibrio, Malonomonas and Caldithrix, suggesting the enhancement of denitrification. Relative high proportions of Desulfotignum and Desulfovibrio, and Sulfurimonas were observed in MCP and H-MCL SCWs, implying that sulfate reduction occurred in SCWs with excess carbon sources. Graphical abstract: Image 1 Highlights: NaOH pretreatment promoted carbon release from MCs in seawater. M-MCL addition intensified nitrogen removal with low effluent COD in SCWs. Carbon sources derived from MCs changed microbial community characteristics of SCWs. Excess MCL addition limited TAN removal and led to sulfate reduction in SCWs.